1994
DOI: 10.2135/cropsci1994.0011183x003400040010x
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Quantitative Trait Loci Using a Small Sample of Topcrossed and F4 Progeny from Maize

Abstract: Plant breeders have an interest in the identification of genomic regions associated with the expression of quantitative traits because they recognize that such information could be used to improve realized heritability and reduce time per cycle of selection. The development of molecular marker technologies may provide tools to accomplish these goals. Maize (Zea mays L.) breeders develop new inbred parents of hybrids through top‐crossed and per se evaluation of numerous quantitative traits in segregating progen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

12
186
4
25

Year Published

1996
1996
2021
2021

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 262 publications
(227 citation statements)
references
References 0 publications
12
186
4
25
Order By: Relevance
“…for heat units to anthesis in Beavis et al (1994) mapped to regions covered by our QTL for days to anthesis on chromosomes 1 and 8, and the effect of the B73 allele at these two QTL were consistent between studies. In addition, Beavis et al (1994) reported five QTL for grain yield (on a per unit surface area basis), three of which mapped to regions associated with barrenness, ear per plant, and yield per plant in our study.…”
Section: Discussionsupporting
confidence: 70%
See 4 more Smart Citations
“…for heat units to anthesis in Beavis et al (1994) mapped to regions covered by our QTL for days to anthesis on chromosomes 1 and 8, and the effect of the B73 allele at these two QTL were consistent between studies. In addition, Beavis et al (1994) reported five QTL for grain yield (on a per unit surface area basis), three of which mapped to regions associated with barrenness, ear per plant, and yield per plant in our study.…”
Section: Discussionsupporting
confidence: 70%
“…In addition, Beavis et al (1994) reported five QTL for grain yield (on a per unit surface area basis), three of which mapped to regions associated with barrenness, ear per plant, and yield per plant in our study. The QTL for grain The ( þ ) indicates that the B73 allele at this QTL increased the value of the trait, (À) indicates that the B73 allele at this QTL reduced the value of the trait.…”
Section: Discussionmentioning
confidence: 58%
See 3 more Smart Citations